The importance of early Christian thought for theology today. : The church in the world - van de Beek, Abraham (Stellenbosch Theological Journal, 2020)
Early Christianity is not only a source of historical interest, it also challenges the systematic theology and Christian ethics of today. Early Christians saw themselves as a community of life with the Eucharist at its centre. Because they participated in eternal life, they were willing to sacrifice their earthly lives in times of persecution and in the care for those who were in mortal danger. As a community of life, they rejected killing any human being, and thus also rejected abortion and military service. They were not an alternative community marked by their diet, dress or emancipation. In such issues they adapted to their environment. They made a difference by their love for those who were in need and by their faithfulness to Christ - though their message was sometimes better than their praxis.